Factors That Trigger Cockroach Density: A Literature Review - Syafii Abudin; Martini Martini; Nurjazuli Nurjazuli (Utan Kayu Publishing, 2023)
Cockroaches are mechanical vectors classified as domestic or peridomestic, In addition to being nuisance pests, there are important medical implications associated with cockroach infestations. For example, cockroaches can transport human pathogenic microorganisms on their bodies and physically or mechanically transfer them to food and food handling surfaces. This study aims to collect the results of previous studies related to the influence of the environment on cockroach infestation density and look at factors that affect cockroach density and population, distribution, infestation levels, and the influence of several parameters that trigger cockroach population dynamics density. This study uses the Literature review method, to summarize the results of previous studies to see the factors that trigger cockroach density. From the results of several studies, it is known that the triggering factors are poor sanitation and pest control practices, old and unmaintained building conditions, poorly managed food availability, socioeconomic status, food handler behavior, incorrect insecticide use and physical environmental conditions including temperature, humidity and lighting. Abstrak: Kecoa merupakan vektor mekanik yang diklasifikasikan sebagai domestik atau peridomestik, Selain menjadi hama pengganggu, ada implikasi medis penting terkait infestasi kecoa. Misalnya, kecoa dapat mengangkut mikroorganisme patogen manusia pada tubuhnya dan secara fisik atau mekanis memindahkannya ke makanan dan permukaan penanganan makanan. Penelitian ini bertujuan mengumpulkan hasil-hasil penelitian sebelumnya yang berkaitan dengan pengaruh lingkungan terhadap infestasi kepadatan kecoa serta melihat faktor yang mempengaruhi kepadatan dan populasi kecoa, distribusi, tingkat infestasi, dan pengaruh beberapa parameter pemicu densitas dinamika populasi kecoa. Penelitian ini menggunakan metode Literature review, untuk merangkum hasil-hasil penelitian sebelumnya untuk melihat faktor pemicu densitas kepadatan kecoa. Dari hasil beberapa penelitian diketahui bahwa faktor pemicu adalah faktor praktik sanitasi dan pengendalian hama yang buruk, kondisi bangunan tua dan tidak terawat, ketersediaan pangan yang tidak dikelola dengan baik, status sosial ekonomi, perilaku penjamah makanan, penggunanaan insektisida yang salah serta kondisi lingkungan fisik baik itu suhu, kelembaban dan pencahayaan.